Facilitation effects of a preparatory skateboard training on the learning of snowbaording - Künzell, S.; Lukas, S. (Kinesiology, 2011)
Surfing`s progeny, snowboarding and skateboarding, present similar positional, visual, and kinesthetic reafferential aspects. Such aspects lead us to the assumption of a positive knowledge transfer from skateboarding to snowboarding. In this investigation we analyzed the probability of and theories for the transfer effect under field conditions. Students of the experimental group received five skateboarding lessons. They then joined a student control group for a six-day school snowboarding trip. Both groups were videotaped on the second and sixth days of the trip. Experts rated snowboarding performance of subjects pertaining to either of groups on a scale of one (very bad) to ten (excellent) points. Inter-rater reliability was very good. While there were no significant differences between the groups on the second day, the students of the experimental group significantly outperformed students of the control group in snowboarding on the sixth day (Mcontrol=4.80, SDcontrol=2.10; Mtreat=6.56, SDtreat=2.10; T=-1.78, df=16, pone-tailed=.045, d=-.83). Given a common underlying structure of skateboarding and snowboarding, skateboarding lessons that develop that structure have a facilitation effect on learning how to snowboard successfully.